2001
DOI: 10.1055/s-2001-919032
|View full text |Cite
|
Sign up to set email alerts
|

Use of MARS in the Treatment of Acute Liver Failure: Preliminary Monocentric Experience

Abstract: SUPPLEMENT nnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnnn n As reported in the literature, the mortality rate for patients with Acute Hepatic Failure (AHF) approaches 80 % in cases in which liver transplantation is not possible.Post transplant mortality depends on the seriousness of the neurological condition at the time of the operation (20 % in I-II degree coma patients and 44 % in III degree coma patients). This is the rationale for extracorporeal depuration treatment, as a bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 0 publications
3
25
0
Order By: Relevance
“…A difficulty that arises when examining the clinical reports presented in the literature on MARS is the inability of this device to support patients up to a spontaneous recovery, with the exception of few cases (17,18). In our series, all patients who were not transplanted died because a life‐threatening infective complication occurred.…”
Section: Discussionmentioning
confidence: 84%
“…A difficulty that arises when examining the clinical reports presented in the literature on MARS is the inability of this device to support patients up to a spontaneous recovery, with the exception of few cases (17,18). In our series, all patients who were not transplanted died because a life‐threatening infective complication occurred.…”
Section: Discussionmentioning
confidence: 84%
“…The highest incidence of liver recovery was observed in patients with ALF due to intoxication 3. Some authors have reported the successful support of patients with ALF before liver transplantation 44. The impact of MARS on the outcome of patients with A-on-C LF is controversial.…”
Section: Liver Support For Patients With Liver Failure: State Of the Artmentioning
confidence: 99%
“…MARS treatment has already been used successfully in patients with EAD in other centers, but to date, the data are limited. Novelli et al 27 reported on six patients, five of whom recovered while receiving MARS treatment. Results of another eight patients, of whom three recovered and four were successfully bridged to OLT, have been reported by Stange et al 14 In the present study, we prospectively enrolled and treated 12 patients who met our inclusion criteria for EAD.…”
Section: Discussionmentioning
confidence: 99%